INCIDENCE OF DENTAL CARIES IN JUNIOR HIGH SCHOOL (SMP) N 1 MUARA KELINGI MUSI RAWAS REGENCY - Januar Perdana; Supli Effendi Rahim; Chairil Zaman (Fakultas Kedokteran Universitas Sriwijaya, 2020)
The increasing case of dental caries among developing country rather than the establish country which showed the decreasing of case. The high incidence of dental caries in children requires optimal handling, especially in preventing the incidence of dental caries in children This research is a quantitative research. The sample in this study is the 7th grade of public junior high school Muara Kelingi students (195 students) using total sampling technique. The data in this study were obtained using secondary data from surveillance data and medical record . Then analyzed using the Chi- Square test. This research was conducted in June 2020 at SMP N 1 Muara Kelingi Kabupaten Musi Rawas. The results showed the variable age (p 0.002), gender variable (p 0.200), knowledge variable (p 0.001), cariogenic food habits variable (p 0.001), nutritional status (p 0.212), toothbrush habit variable (p 0.015). and variable utilization of service facilities (p 0.002). In the multivariate analysis, it was found that the most dominant variable associated with the incidence of dental caries was the habit of toothbrushes with a p value of 0.012. Based on the research results, it is necessary to have facilities and information related to dental health and the need for support and an active role from parents.